The analysis of the state of pharmaceutical provision of patients with hepatitis B and C according to public procurement of medicines - Nozdrina, A. A.; Volkova , A. V. (Social Pharmacy in Health Care, 2023)
Aim. To analyze the state of pharmaceutical provision of patients with hepatitis B (HB) and C (HC) according to public procurement of medicines. Materials and methods. The materials of the study were data from the Prozorro Public Procurement System, the Public Health Center of the Ministry of Health of Ukraine, the State Register of Medicines of Ukraine, the Unified Clinical Protocols for Primary, Secondary (Specialized), Tertiary (Highly Specialized) Medical Care “Viral Hepatitis C in Adults” and “Viral Hepatitis B in Adults”, and the Clinical Guideline “Viral Hepatitis B”». The study used methods of content analysis, comparative analysis and logical generalization of the results using the graphical method, as well as mathematical and statistical methods of analysis. Results. It was determined that during the period of 2017-2021, the maximum expenditures for the procurement of direct-acting antiviral drugs (DAAs) was recorded in 2017 and amounted to UAH 48.4 million. The amount of procurement in 2018 was 89 % less compared to the previous year. In 2019, the maximum rate (%) of growth in the cost of purchasing medicines for the treatment of HS compared to the previous period was 401 %. In 2020-2021, there was a gradual decrease to the minimum amount of UAH 2.4 million in 2021. According to the results of the analysis of procurement of medicines for the treatment of HS in physical terms after a significant decrease in 2018, in 2019 and 2020, there was a considerable increase and the purchase of the maximum number of packages in 2020 (12 thousand); in 2021, the minimum number of medicines (1050 units) was purchased for the entire period of analysis. It was determined that the structure of public procurement in 2017 and 2018 was dominated by original medicines of the groups J05AP08 Sofosbuvir and J05AP51 Sofosbuvir and Ledipasvir. In 2017, their share in the total volume of purchases in monetary terms amounted to 96.9 %, and in 2018 – 63.9 % of the total amount. However, starting from 2019, procurement of generic drugs in these groups prevailed, which had a share of 62.8 % in 2019, 48.3 % in 2020, and 79.2 % of the total monetary value of procurement in 2021. The dominance of the number of foreign-made drugs in the structure of the purchased drug range was noted (in monetary terms, from 97.8 % of the total expenditures in 2020 to 99.98 % in 2017). Drugs of domestic production were represented by only 2 trade names (TN), namely Livel manufactured by Valartin Pharma LLC in 2017-2018 and Ribavirin manufactured by Astropharm LLC in 2018-2020. According to the results of the ABC analysis, it was proven that each year Group A included groups J05AP51 Sofosbuvir and Ledipasvir and J05AP08 Sofosbuvir (2018, 2021-Group B). Group J05AP01 Ribavirin used as adjunctive therapy for HC complications was included in group C in 2017-2021, except in 2018, when the number of drugs purchased was increased from 1 to 3 TN. The unstable nature of procurement of medicines for the treatment of HB was revealed: from UAH 18.5 million in 2017 to UAH 707.8 thousand in 2021; during the period of 2018-2020, the purchase amount averaged UAH 2.5 million. It was determined that in 2021, compared to 2017, a decrease in this indicator was recorded by more than 85 %. Less than 50 % of the country’s regions procured medicines for the treatment of HB, and only 14 regions procured medicines through a centralized mechanism. Annual procurement took place in only 5 regions, namely Vinnytsia, Zakarpattia, Ivano-Frankivsk, Kyiv and Lviv. The largest number of TN of medicines was procured by the Kyiv region (7 TN in 2017 in the amount of UAH 52.3 million and 8 TN in 2020 in the amount of UAH 22.6 million). Conclusions. Summarizing the results of the study, it should be noted that there is a clear downward trend in centralized procurement throughout the entire study period, which, when considered in the dynamics of subsequent years, cannot contribute to achieving the goals for the elimination of viral hepatitis by 2030. However, the transition to decentralized procurement and tenders through the state enterprise “Medical Procurement of Ukraine” should contribute to the opportunity to purchase the required number of courses of medicines under the state program and increase the number of people who participate in it every year.